2016
DOI: 10.1177/0266242616654957
|View full text |Cite
|
Sign up to set email alerts
|

Appropriation strategies and open innovation in SMEs

Abstract: Drawing upon data from the 5th UK innovation survey, our goal is to shed light on how management choices on the nature of appropriation relate to management choices on the degree of openness within SMEs. To this end, our findings indicate a threshold effect of both informal and formal appropriation mechanisms on the likelihood of engaging in both coupled and inbound open innovation. That is, an emphasis on appropriation appears to be important in shifting firms from a closed to an open strategy. There is, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 62 publications
6
80
0
8
Order By: Relevance
“…Bigliardi and Galati [67] found that factors, such as insufficient knowledge, little experience of collaboration, lack of funds and the absence of organization, hinder the adoption of open innovation for SMEs. Freel and Robson [68] emphasized that informal intellectual property affects SMEs to absorb knowledge through open innovation.…”
Section: Strategic Alliancementioning
confidence: 99%
“…Bigliardi and Galati [67] found that factors, such as insufficient knowledge, little experience of collaboration, lack of funds and the absence of organization, hinder the adoption of open innovation for SMEs. Freel and Robson [68] emphasized that informal intellectual property affects SMEs to absorb knowledge through open innovation.…”
Section: Strategic Alliancementioning
confidence: 99%
“…A területen végzett kutatómunka igyezett feltárni a nyitottságot mozgató vagy akadályozó tényezőket. Ezek alapján a cégméretet (Barge Gil, 2010;Harison & Koski, 2010;Brunswicker & Chesbrough, 2018), a tulajdonosi struktúrát (Harison & Koski, 2010), a kiegészítő eszközök, szellemi tulajdonjog-alapú eszközök és hálózati hatások szerepét (Bonaccorsi et al, 2006;Henkel, 2006;Sebrek, 2019), az aspirációs szintet (Alexy et al, 2016), a K+F intenzitást (Barge Gil, 2010), a tudásfelhasználhatóság mértékét (Laursen & Salter, 2014;Freel & Robson, 2017), a termékinnovációs híresztelések hatását (Hannigan et al, 2018), vagy a külső környezetből fakadó technológiai lehetőségeket (Klevorick et al, 1995) vizsgálták. Jelen kutatás a tágabb szakirodalom és az üzleti sajtó alapján további tényezők feltárására irányul, amelyek felölelik a méretgazdaságosság jelentette versenynyomást, a termékportfólió innovációs fokát, a pénzügyi innovációs mozgástér meglétét, illetve a belső vállalati műveletek és folyamatok átalakítási fokát a nyitott innovációs törekvések magyarázatában (Alexy et al, 2013;Chesbrough, 2007;Chiaroni et al, 2011;Dobrev & Carroll, 2003;The Economist, 2011a).…”
Section: Elméleti Háttérunclassified
“…Korábbi munkák többnyire a cégméret, a kiegészítő eszközök, az aspirációs szint, a K+F intenzitás, vagy hálózati hatások szerepét tanulmányozták (Alexy et al, 2016;Barge Gil, 2010;Brunswicker & Chesbrough, 2018;Bonaccorsi et al, 2006;Harison & Koski, 2010;Henkel, 2006). Újabb munkák a területen a tudásmegtartási stratégiák (Freel & Robson, 2017), a szellemi tulajdonjog-alapú eszközök (Sebrek, 2019) és a termékinnovációs pletykák (Hannigan et al, 2018) nyitott innovációra gyakorolt befolyását vizsgálták.…”
unclassified
“…In order to penetrate a global market, firms need to be knowledgeable about its attributes and learn from competitors and partners alike with respect to innovation of technology and services (Narula, 2004). Positive consequences of OI include: 1) benefits of sharing information and knowledge with external sources; 2) the ability to share risk with partners; 3) help to solve problems from partners; 4) a larger amount of resources available; and 5) synergies among partners for developing technology and product (Ahuja, 2000;Archibugi & Iammarino, 2002;Narula, 2004;Overby, 2005;Massa & Testa, 2008;Su et al, 2009;Wincent et al, 2010;Huang & Yu, 2011;Michelfelder & Kratzer, 2013;Un & Asakawa, 2015;Freel & Robson, 2017;Lin & Lin, 2016).…”
Section: Consequences Of Open Innovationmentioning
confidence: 99%